Hammond’s Cube Evaluation Model Adapted to Current Conditions: Is It Appropriate? - Ryan Angga Pratama (Scientia Publica Media, 2025)
In the original model of “Hammond’s Evaluation Cube (1967)”, educational evaluation focused on three main dimensions: (a) Behavior, consisting of Cognitive, Affective, and Psychomotor aspects, (b) Instruction, consisting of Organization, Content, Method, Facilities, and Cost, (c) Institution, consisting of Student, Teacher, Administrator, Education Specialist, Family, and Community, with a 3×5×6 evaluation structure, resulting in a total of 90 evaluation cells. However, with the dynamic changes in education in the era of technology, the 21st-century global demands, and developments related to the Industrial Revolution 4.0 and Society 5.0, the author proposes further development of this model to make it more relevant in the modern educational context. The method used is a critical analysis and literature review of Hammond’s Evaluation Cube (1967), with an emphasis on the relevance of the model to current educational developments. The findings produced are that the author offers an updated model with three main dimensions: (a) Behavior, consisting of Cognitive, Affective, and Psychomotor aspects, (b) Instruction, consisting of Organization, Content, Method, Facilities, and Cost, (c) Institution, consisting of Student, Teacher, Administrator, Education Specialist, Family, Community, AI and Data Specialist, Technology/IT Support, and Policies/Regulations, with a 3×5×9 evaluation structure, resulting in a total of 135 evaluation cells. The implication of this study is that the “Hammond Evaluation Cube Adapted to Current Conditions (2025)” can be a richer and more relevant evaluation model for modern education. This model can help educational institutions identify needs, strengths, and challenges in technology integration and in preparing students for an evolving future.